Manly Sea Eagles : the team they love to beat - Chesterton, Ray (Chatswood, NSW : New Holland Publishers Pty Ltd, 2016)
The Manly-Warringah Sea Eagles are the most-maligned rugby league club in Australia. Situated on Sydney’s trendy North Shore the Sea Eagles, as they are generally known, have been publically derided for decades for apparent ‘chequebook’ recruitment in search of premiership success. Manly have gone on to win titles in every decade since the 1970s, but the club still has its critics and detractors. Respected Sydney journalist Ray Chesterton (The Sun, The Daily Telegraph) chronicles the controversies, the intrigue and the petty jealousies that have plagued the club over its long history, highlighting all the great names and laying bare the challenges the now privately-owned club has faced in recent years. One thing is clear... the Manly-Warringah Sea Eagles are still the team they love to beat!
Includes bibliographical references (page 307).
Keywords: Manly-Warringah Sea Eagles (Rugby team).; Rugby League football -- New South Wales -- Sydney -- History; Australian